2017
DOI: 10.1002/jsfa.8276
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sugar content and related enzyme activities in table grape (Vitis vinifera L.) in response to foliar selenium fertilizer

Abstract: AI played an important role in the process of sugar accumulation in berries; high AI activity in berries and photosynthetic rate in leaves could explain the mechanism by which Se fertilizer affected sugar accumulation in berries. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 42 publications
4
30
0
3
Order By: Relevance
“…In this study, the changes in glucose and fructose contents in roots, stems, and leaves of grape seedlings were basically consistent with the changes of invertase activities in those organs, and AI activity was much higher than NI activity, consistent with previous studies [63][64]. Studies have shown that AI is an important enzyme for sugar accumulation in grape berry [60,65]. In the present study, AI activity in roots, stems, and leaves of grape PLOS ONE seedlings was increased in all the MT treatments, indicating that AI is also a key enzyme for the growth and development of vegetative organs of grape seedlings.…”
Section: Mt Stimulated Enzymes Related To Sucrose Metabolism To Incresupporting
confidence: 91%
“…In this study, the changes in glucose and fructose contents in roots, stems, and leaves of grape seedlings were basically consistent with the changes of invertase activities in those organs, and AI activity was much higher than NI activity, consistent with previous studies [63][64]. Studies have shown that AI is an important enzyme for sugar accumulation in grape berry [60,65]. In the present study, AI activity in roots, stems, and leaves of grape PLOS ONE seedlings was increased in all the MT treatments, indicating that AI is also a key enzyme for the growth and development of vegetative organs of grape seedlings.…”
Section: Mt Stimulated Enzymes Related To Sucrose Metabolism To Incresupporting
confidence: 91%
“…In addition, Se fertilizer application decreased the titratable acidity of grape berries (Table 2), which was also confirmed in kumquat fruit [42], at the same time increased the fruit sugar-acid ratio. Soluble sugars and soluble proteins in grape berries under Se fertilizer treated was higher compared to that of CK, it may be due to the high photosynthetic rate of Se fertilizer application, also it was confirmed in our previous study [43,44], which was focused on changes of sugars content in response to foliar Se fertilizer, the results showed that the high acid invertase of grape berries and the high photosynthetic rate of leaves explained the increasing of soluble sugars in grape berries with foliar spray Se fertilizer. In addition, there were almost no reports about the impact of Se fertilizer on RES and OPC content in grape berries except our previous study [7], so this study was more necessary.…”
Section: Effect Of Foliar Se Fertilizer On Fruit Quality At Maturitysupporting
confidence: 80%
“…The growth and development of fruit include the whole process from fertilization to fruit growth, maturation and senescence, and it is also the process of continuously accumulating and transforming nutrients and fruit morphogenesis construction 41. During the fruit growth and development process, the accumulation of nutrients mainly includes carbohydrates, proteins and lipids, most of which are transported by other organs of the plant, such as roots and leaves, while carbohydrate metabolism is the basis of regulation in its process 42, 43. During the early stages of Camellia oleifera fruit development, carbohydrates come from the photosynthesis of leaves and fruits 44.…”
Section: Discussionmentioning
confidence: 99%